NRF 24L01 SEBAGAI PEMANCAR/PENERIMA UNTUK WIRELESS SENSOR NETWORK - W, Alessandro Septiano; Gozali, Theresia (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2020)
Internet of Things (IoT) as part of a wireless sensor that requires data transmission with a frequency band of 15 kHz can use the NRF 24L01 device. In this paper we will see the ability of NRF 24L01 devices for sending audio data .  Transmission of audio data requires a transmitter and receiver (transceiver) with low power consumption. The NRF24L01 wireless communication module has the Ultra Low Power (ULP) feature, so it can last a long time with relatively low power consumption. This design can function optimally in a limited area, such as in 1 room. Audio data sent from the sending device (arduino and NRF 24L01) will be received by the receiving device (arduino and  NRF24L01), then it is converted to loudspeakers . Test results show good quality Audio data can be heard at a distance of 10 m.